High speed flow characteristics in gun tunnel - Ahmed D.I.; Yusoff M.Z.; Amir A.-F.; Kasolang S. (2023)
An experimental study was performed to establish investigation on the transient flow in short duration high speed flow gun tunnel test facility available in Universiti Tenaga Nasional (UNITEN). Physical description of the facility along with the principle of operation is described. The pressure history of flow process was captured using fast response pressure transducer at three stations located at the end of the facility. Experimental measurements of shock strength, peak pressure and shock wave speed change of Air-Air as a driver/driven gas are then presented and compared with another set of experimental measurements using gas combination of Helium-Air. Shock wave speed now can be measured experimentally with the two pressure transducers technique easily. The existence of the piston has a very significant influence on the moving shock wave and peak pressure value achieved. The results provide very good estimate for the above mentioned parameters obtained after diaphragm rupture and also provide better understanding of the parameters that affect the performance of the facility. 2012 American Institute of Physics.